TENGBALL GAME LEARNING MODEL TO IMPROVE STUDENTS’ PHYSICAL FITNESS - Syofi Rubik Nasrulloh; Harwanto Harwanto; Hari Karyono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
Tengball as one of the optional traditional games in learning Physical Education in the fort-like game which is modified by using a ball and referring to the content of educational objectives including developing self-management skills in the development and maintenance of physical fitness and healthy lifestyles through various physical activities and the chosen sport. The purpose of this study was to develop tengball game model to improve the students’ physical fitness at MI Tarbiyatul Islamiyyah Panjunan Sukodono. This research was development research. The subjects were students of MI Tarbiyatul Islamiyyah Panjunan Sukodono. The methods used were questionnaires and tests. The instrument used was a learning model validation questionnaire, response questionnaire, and performance tests. The results showed that tengball game model was valid according to the validation results, positive user responses, and tengball game model was effective in improving students' physical fitness.